2013
DOI: 10.3109/09513590.2013.867320
|View full text |Cite
|
Sign up to set email alerts
|

Relation of antimullerian hormone with the clinical signs of hyperandrogenism and polycystic ovary morphology

Abstract: The relation of antimullerian hormone (AMH) levels with the clinical and biochemical markers of polycystic ovary syndrome (PCOS) could be different. A total of 463 PCOS patients were evaluated in this cross-sectional study. Groups were constructed according to polycystic ovarian morphology (PCOM) and menstrual cycle-length. The relation of serum AMH with androgenic hormones, menstrual cycle-length and clinical signs of PCOS were investigated. A powerful positive relation was found between the PCOM and AMH leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…33 Various studies have found a high sensitivity and specificity of AMH in the diagnosis of PCOS with a cutoff value ranging from 3.34 to 4.7 ng/mL. 26,29,30 In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 ( Table 4) which is similar to another study from India (3.34 ng/mL). 30 AMH has been assessed for diagnosis of PCOS with reference to the major classifications of PCOS.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…33 Various studies have found a high sensitivity and specificity of AMH in the diagnosis of PCOS with a cutoff value ranging from 3.34 to 4.7 ng/mL. 26,29,30 In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 ( Table 4) which is similar to another study from India (3.34 ng/mL). 30 AMH has been assessed for diagnosis of PCOS with reference to the major classifications of PCOS.…”
Section: Discussionsupporting
confidence: 88%
“…It is essential to determine the cutoff points of AMH in various populations and ages as there is an age‐dependent decline in values of AMH . Various studies have found a high sensitivity and specificity of AMH in the diagnosis of PCOS with a cutoff value ranging from 3.34 to 4.7 ng/mL . In our study, 100.00% sensitivity and 95.83% specificity were seen with a cutoff value of 3.6 (Table ) which is similar to another study from India (3.34 ng/mL) …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As serum AMH correlates well with the polycystic appearance of ovaries on ultrasound, several studies are proposing to set thresholds by AMH as an alternative to ultrasound [44 ▪ ,46 ▪▪ ,48]. Recent evidence in 463 PCOS women suggests that serum AMH may provide insight into the subphenotypes of PCOS with higher serum AMH predicting longer menstrual cycle length, higher luteinizing hormone (LH) levels, and hirsuitism [51 ▪▪ ]. Clearly, markedly elevated age-specific AMH correlates with the clinical diagnosis and severity of PCOS and may eventually be adopted as a diagnostic criteria for PCOS.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%